Capacity Enhancement of Nuclear Medicine Facilities: Renovation of Institute of Nuclear Medicine and Allied Sciences (INMAS), Rangpur (Bangladesh Journal of Nuclear Medicine, 2026)
The increasing demand for diagnostic and therapeutic nuclear medicine services in northern Bangladesh necessitated the capacity enhancement and modernization of the Institute of Nuclear Medicine and Allied Sciences (INMAS), Rangpur. This technical case study presents a comprehensive overview of the renovation project aimed at upgrading infrastructure, improving workflow efficiency, and expanding clinical service capabilities. The renovation involved strategic redesign of facility layout, installation of advanced imaging equipment, enhancement of radiation safety measures, and optimization of patient management systems. Key interventions included the modernization of gamma camera and SPECT systems, the establishment of dedicated hot labs and radiopharmacy units, and improvements in shielding, ventilation, and waste management systems in compliance with international safety standards. A systematic methodology involving needs assessment, planning, implementation, and evaluation was adopted for the project, which highlighted human resource development through training for medical physicists and technologists. The upgraded facility allowed for advanced NM procedures and better patient accessibility, alongside improved radiation protection. This case study underscores the significance of integrated planning and regulatory adherence in facility upgrades, positioning INMAS Rangpur as a model for similar initiatives in resource-constrained environments.Bangladesh J. Nuclear Med. 28(2): 356-358, July 2025